Deep Time, Dark Times : On Being Geologically Human - Wood, David (Book collections on Project MUSE., 2018)
The new geological epoch we call the Anthropocene is not just a scientific classification. It marks a radical transformation in the background conditions of life on Earth, one taken for granted by much of who we are and what we hope for. Never before has a species possessed both a geological-scale grasp of the history of the Earth and a sober understanding of its own likely fate. Our situation forces us to confront questions both philosophical and of real practical urgency. We need to rethink who "we" are, what agency means today, how to deal with the passions stirred by our circumstances, whether our manner of dwelling on Earth is open to change, and, ultimately, "What is to be done?" Our future, that of our species, and of all the fellow travelers on the planet depend on it.The real-world consequences of climate change bring new significance to some very traditional philosophical questions about reason, agency, responsibility, community, and man's place in nature. The focus is shifting from imagining and promoting the "good life" to the survival of the species. Deep Time, Dark Times challenges us to reimagine ourselves as a species, taking on a geological consciousness. Drawing promiscuously on the work of Nietzsche, Heidegger, Foucault, Derrida, Deleuze, and other contemporary French thinkers, as well as the science of climate change, David Wood reflects on the historical series of displacements and de-centerings of both the privilege of the Earth, and of the human, from Copernicus through Darwin and Freud to the declaration of the age of the Anthropocene. He argues for the need to develop a new temporal phronesis and to radically rethink who "we" are in respect to solidarity with other humans, and responsibility for the nonhuman stakeholders with which we share the planet. In these brief, lively chapters, Wood poses a range of questions centered on our individual and collective political agency. Might not human exceptionalism be reborn as a sort of hyperbolic responsibility rather than privilege?